Trichosanthes tricuspidata Lour. dari Kabupaten Jember, Jawa Timur - Ulum, Fuad bahrul; Wiyono, Hidayat teguh; Setyati, Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2022)
Trichosanthes, one of the largest genera of Cucurbitaceae with in species and sub-species diversity offers a broad study for the systematic and taxonomy and also for the phytochemistry and conservation especially for the local specimen. The aims of this study were to determine the specimen and provided the information of medicinal uses and potency, also the conservation strategy. Determination was conducted by literature and confirmation to the experts, while the medicinal and conservation studied with literature review. The taxonomic investigation through the morphological of specimen collected from Jember, East Java represented Trichosanthes tricuspidata Lour. Medicinal potencies of the species were for threatment of imflamation, worm infection, migrain, and fever. Conservation action via habitat protection, species exploration, seed production, breeding activities were purposed for the flora sustainability.